(3GdMb ai GdMHS chSjdI ddVeGf (B: s (3OQGSI ebGQfI Hjf GdbGfhfjf GdYQGbj h GdeUQj h GdTQjYI GdES`dGej`I (B/ s - (3geGe eMeO jYbhHs; (3MSjf MGeO MSGf s; (3SYjO SdjeGf LHQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3h bO HOG gPG GdfXGe ai ebOeI GdHMK eThHkG HGdGVWQGH(B: (3h ZjQ hGVM GdeYGde h YOe eYQaI fWGbg h CMcGeg(B: (3h dcf eY JhGdi UaMGJ GdHMK HOG gPG GdfXGe HGdGSJbQGQ h hVhM GdeYGde(B: (3h age fWGbg h Pdc HYO GdJYQja HeGgjI gPG GdfXGe h eG jJQJH Ydjg ef CMcGe(B. (3GYJeOoJ NdGd gPg GdOQGSI Ydi efgL GdebGQfI(B: (3h Pdc ef NdGd YQV fUhU GdbGfhfjf GdeOfjjf GdYQGbi h GdeUQi h ebGQfJgeG HGdabg GdES`dGei(B: (3eY HjGf ChLg GdGJaGb h GdGNJdGa HjfgeG(B: (3h bO BK`QfG YOe SQO MGdGJ JWHjbjI; fXQkG dCfgG dG JJfGgi(B: (3h EfeG GbJUQJ Ydi HjGf CMcGeg(B: (3h HYO Pdc HjGf eLGd JWHjbg(B: (3h GdeJeKd ai fWGb GdMb ai GdMH`S(B: (3h Pdc YfO GdcdGe Yf TQW YdGbI GdGQJHGW Hjf GdJRGe GdeMHhS h GdBN`Q GdeVehf HGdMHSs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2016.s
(3HHdjhLQGajG(B: (3UaMGJ (B381-400.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdMb aj GdMHSs; (3GdQgfs; (3GdTQjYI GdESdGejIs; (3GdGMJLGL HGdMb aj GdMHS Ydi GdZjQs; (3GdaSNs; (3fXGe GdXaQs; (3fXGe GdMLR JMJ jO GdfaSs; (3GdebGUIs; (3GdOGFfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs